2022
DOI: 10.1136/bmjopen-2021-056475
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence against women with disability and associated mental health concerns: a cross-sectional survey in Mumbai, India

Abstract: ObjectivesThe risk of intimate partner violence (IPV) against women with disability is believed to be high. We aimed to compare the prevalence of past-year IPV against women with and without functional difficulties in urban informal settlements, to review its social determinants and to explore its association with mental health.DesignCross-sectional survey.SettingFifty clusters within four informal settlements.Participants5122 women aged 18–49 years.Primary and secondary outcome measuresWe used the Washington … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 92 publications
(140 reference statements)
1
6
0
1
Order By: Relevance
“…For the individual level factors, married women with functional difficulty were found to have a higher likelihood of accepting domestic violence. This finding aligns with previous literature [44][45][46] emphasizing the double vulnerability of women with functional difficulty and their acceptance to domestic violence. It is important to note that approximately 10% of the Iraqi population live with one or more disabilities, with nearly two million of them being women of reproductive age [47].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For the individual level factors, married women with functional difficulty were found to have a higher likelihood of accepting domestic violence. This finding aligns with previous literature [44][45][46] emphasizing the double vulnerability of women with functional difficulty and their acceptance to domestic violence. It is important to note that approximately 10% of the Iraqi population live with one or more disabilities, with nearly two million of them being women of reproductive age [47].…”
Section: Discussionsupporting
confidence: 92%
“…This was determined using a set of questions focused on six domains: seeing, hearing, walking, self-care, communication, and remembering. If a woman experienced any of these difficulties, it was classified as (yes) for functional difficulties; Otherwise, it was classified as (no) [43]. Additionally, Exposure to mass media had been created based on reading a newspaper, listening to the radio, or watching television.…”
Section: Study Variablesmentioning
confidence: 99%
“…As noted above, research suggests extent frameworks may not be applicable outside of the western context they were developed in (Hayes et al, 2021 ; VanderEnde et al, 2012 ). Among the few studies which have examined IPV risk among persons with disabilities in India, Riley and colleagues ( 2022 ) found that those with disabilities within Mumbai had a greater risk of IPV. This item was nevertheless limited to disability in general (i.e., yes/no disability).…”
Section: India and Ipvmentioning
confidence: 99%
“…This sensory difference may exacerbate risk of IPV for Blind respondents. Collectively, these items allow us to explore IPV vulnerability among marginalized women who may not experience such severe disabilities that they are institutionalized (Human Rights Watch, 2014 ) but who nonetheless may be at greater risk (Breiding & Armour, 2015 ; Riley et al, 2022 ).…”
Section: India and Ipvmentioning
confidence: 99%
See 1 more Smart Citation